Artificial Intelligence Challenges - Autonomous cars: A brief review: Artificial Intelligence Challenges - Autonomous cars: A brief review (Innovation & Development in Engineering and Applied Science, 2023)
This documentary-descriptive research aims to explore the advancement of artificial intelligence (AI) in selfdriving vehicles and its impact on the benefit  of society. While it is undeniable that  self-driving vehicles have practically become a technological reality in the  field of computing, both at present and in the foreseeable future.  However, several apparent  problematic aspects need to be  addressed in terms of legislation, as  autonomous cars are set to become an integral part of everyday life. Therefore, this research examines  through a literature review the  significant advances and efforts  devoted to software design in this area of study focused on the operation of autonomous vehicles in urban  environments and their ability to  circumvent city obstacles as well as  challenges to unforeseen eventualities.
Keywords: Self-driving cars; Challenges; Decision-making; Safety and reliability; Human-machine interaction